Maternal source of variability in the embryo development of an annual killifish. (18th January 2017) - Polačik, M.; Smith, C.; Reichard, M.
Abstract: Organisms inhabiting unpredictable environments often evolve diversified reproductive bet‐hedging strategies, expressed as production of multiple offspring phenotypes, thereby avoiding complete reproductive failure. To cope with unpredictable rainfall, African annual killifish from temporary savannah pools lay drought‐resistant eggs that vary widely in the duration of embryo development. We examined the sources of variability in the duration of individual embryo development, egg production and fertilization rate in Nothobranchius furzeri . Using a quantitative genetics approach (North Carolina type II design), we found support for maternal effects rather than polyandrous mating as the primary source of the variability in the duration of embryo development. The number of previously laid eggs appeared to serve as an internal physiological cue initiating a shift from rapid‐to‐slow embryo developmental mode. In annual killifish, extensive phenotypic variability in progeny traits is adaptive, as the conditions experienced by parents have limited relevance to the offspring generation. In contrast to genetic control, with high phenotypic expression and heritability, maternal control of traits under natural selection prevents standing genetic diversity from potentially detrimental effects of selection in fluctuating environments.